Current role of melatonin in pediatric neurology: Clinical recommendations. (March 2015) - Bruni, Oliviero; Alonso-Alconada, Daniel; Besag, Frank; Biran, Valerie; Braam, Wiebe; Cortese, Samuele; Moavero, Romina; Parisi, Pasquale; Smits, Marcel; Van der Heijden, Kristiaan; Curatolo, Paolo
Abstract: Background/purpose: Melatonin, an indoleamine secreted by the pineal gland, plays a key role in regulating circadian rhythm. It has chronobiotic, antioxidant, anti-inflammatory and free radical scavenging properties. Methods: A conference in Rome in 2014 aimed to establish consensus on the roles of melatonin in children and on treatment guidelines. Results and Conclusion: The best evidence for efficacy is in sleep onset insomnia and delayed sleep phase syndrome. It is most effective when administered 3–5 h before physiological dim light melatonin onset. There is no evidence that extended-release melatonin confers advantage over immediate release. Many children with developmental disorders, such as autism spectrum disorder, attention-deficit/hyperactivity disorder and intellectual disability have sleep disturbance and can benefit from melatonin treatment. Melatonin decreases sleep onset latency and increases total sleep time but does not decrease night awakenings. Decreased CYP 1A2 activity, genetically determined or from concomitant medication, can slow metabolism, with loss of variation in melatonin level and loss of effect. Decreasing the dose can remedy this. Animal work and limited human data suggest that melatonin does not exacerbate seizures and might decrease them. Melatonin has been used successfully in treating headache. Animal work has confirmed a neuroprotective effect of melatonin, suggesting a role in minimising neuronal damage from birth asphyxia; results from human studies are awaited. Melatonin can also be of value in the performance of sleep EEGs and as sedation for brainstem auditory evoked potential assessments. No serious adverse effects of melatonin in humans have been identified.